Fertility after uterine artery embolization: a review. Issue 1 (2nd January 2016) - McLucas, Bruce; Voorhees III, William D.; Elliott, Stephanie
Abstract: Uterine artery embolization (UAE) research has largely been focused on women over 40 years, yet women of reproductive age undergo UAE without any increased morbidity. Some physicians refrain from recommending UAE to women in this age group because of some research findings showing a negative effect on fertility. This review presents a comprehensive discussion of the fertility potential of women undergoing UAE, in terms of pregnancy rates and complications as well as ovarian function and reserve. Findings indicate many benefits for women desiring fertility who undergo UAE over traditional myomectomy.